Prompt charm production in pp collisions at √s=7 TeV - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Nuclear physics. B, Particle physics, 2013)
Charm production at the LHC in pp collisions at s=7 TeV is studied with the LHCb detector. The decays D0→K−π+, D+→K−π+π+, D⁎+→D0(K−π+)π+, Ds+→ϕ(K−K+)π+, Λc+→pK−π+, and their charge conjugates are analysed in a data set corresponding to an integrated luminosity of 15 nb−1. Differential cross-sections dσ/dpT are measured for prompt production of the five charmed hadron species in bins of transverse momentum and rapidity in the region 0<pT<8 GeV/c and 2.0<y<4.5. Theoretical predictions are compared to the measured differential cross-sections. The integrated cross-sections of the charm hadrons are computed in the above pT-y range, and their ratios are reported. A combination of the five integrated cross-section measurements givesσ(cc¯)pT<8 GeV/c,2.0<y<4.5=1419±12(stat)±116(syst)±65(frag) μb, where the uncertainties are statistical, systematic, and due to the fragmentation functions.
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 585
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 19.03.2021